A TREATMENT OF DISTRIBUTION COSTS. - Woodbury, W. F. (The Accounting Review, 1927)
Abstract The division of the profit and lose statement devoted to distribution costs is receiving much attention of late, and rightly so, as, in many companies, the cost of distribution is seemingly way out of proportion to the manufacturing cost of the product which is being distributed. Furthermore, from the statistics which are being gathered by different bodies it appears that not only is the cost of distribution generally heavy, but that it is tending to make up an even larger proportion of total cost as time goes on. Distribution costs depend entirely on the nature of the business and the variety of the product. It appears that the time is past for asking the question: Can we produce all the sales department can sell? That has come to be a comparatively easy matter with most industries and in fact the pendulum has long since swung to the other extreme. With the extraordinary development of modern machinery it is going to be an ever increasing task for the sales department to dispose of all the factory can manufacture. This being the case, it is natural that distribution costs should continue to creep higher proportionately. Management is, undoubtedly, realizing that the big problem before it is not only to dispose of what can be manufactured but to dispose of it economically so that in the sale thereof a profit will be maintained.